'On a road to nowhere….' analyzing motivations for undirected travel. (September 2022) - Hook, Hannah; De Vos, Jonas; Van Acker, Veronique; Witlox, Frank
Highlights: Four main motivations were found for undirected travel by factor analysis. Strongest travel motivations were found for active modes. Motivation for undirected travel has clear relationships to physical/mental health. The use of multiple modes is most likely to satisfy motivations. The longer an undirected trip is, the more fulfilling it seems to be. Abstract: This study is the first to empirically analyze motivations for taking undirected travel (UT) trips, or travel without a destination (as opposed to derived trips) undertaken for the purpose of the trip itself, as the determinants and characteristics are largely unknown. The overall research objective is to explore UT motivations in terms of demographics and trip characteristics, such as mode, frequency, distance, and duration, using survey data from Flanders, Belgium during the COVID-19 pandemic lockdown (18 March – 4 May 2020). First, a factor analysis identifies four main motivations for UT: 1. Improving Health and Well-Being, 2. Removing Negative Feelings, 3. Enjoying Scenery, and 4. Out-of-Home Socializing. Following, differences in UT motivations across groups are analyzed with mean-comparisons of demographic characteristics, trip characteristics, and attitude and well-being measurements. Findings suggest a clear relationship between UT and physical/mental health. There are stronger motivations for active than motorized UT trips, and stronger motivations associated with use of multiple modes. Longer (distance and duration) and more frequent UT trips increasingly fulfill all motivations. This research provides more evidence for the idea that travel is not always a derived demand for which less is always better, or an ancillary event to other activities, and can offer baseline empirical information on UT from which future studies can grow as well as contribute information about the value of travel.